A study of evolution and trend of permissions for Android applications - Huang, Zhenwei (2015)
Mobile security becomes an important issues when mobiles devices and services gets popular over the decades. Many device OS platform especially Android based is growing tremendously due to the collaboration from the handset alliance. One of the major factor has to begin with Android application package permission. The properties of permission enable users to access mobile devices. Confidential and sensitive information may easily be dupe by these permissions. APK applications’ permission set may be misuse and sabotage by mobile software developers or hackers by deliberately modifying them. Project findings indicate the behaviour of permissions release by third party application store.